Nurses' conduct in terms of reception and risk classification in obstetric urgencies and emergencies: An integrative review (Research, Society and Development, 2023)
The aim of this study is to provide evidence from the scientific literature of the importance of nurses applying risk classification in obstetric urgencies and emergencies. This is an Integrative Literature Review. The search and selection of studies were carried out in the LILACS, BDENF, MEDLINE, IBECS and Coleciona SUS databases. The time frame established was the period from 2018 to 2023. The analysis of the selected articles highlighted the indispensability of filling in the information collected during Reception and Risk Classification in the patient's record, so that there can be a broad and reliable analysis of the applicability of the instrument during care, enabling the professional's perception of the particularities of the pregnant woman, her individualities and the patient's risk conditions that require attention. The synthesis of the data revealed issues related to delays in care, which have a direct impact on the organization of care flows, causing overcrowding in the health system and an increase in maternal morbidity and mortality rates.